KARAKTERISTIK HUKUM OTONOM DAN IMPLIKASINYA DI INDONESIA (Model Penegakan Hukum Prosedural Pada Sistem Peradilan Pidana) - S Sahabuddin (Universitas Batanghari Jambi, 2018)
The life of the law has been, not logic, but experience law will not be found by a mere examination of theoretical rules; concentration on those rules alone harms the legal profession since it leads to the ignoring of the wider context which gives law its true social significance